2014
DOI: 10.1111/mmi.12800
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osmotic stress on protein diffusion in Lactococcus lactis

Abstract: SummaryWe measured translational diffusion of proteins in the cytoplasm and plasma membrane of the Grampositive bacterium Lactococcus lactis and probed the effect of osmotic upshift. For cells in standard growth medium the diffusion coefficients for cytosolic proteins (27 and 582 kDa) and 12-transmembrane helix membrane proteins are similar to those in Escherichia coli. The translational diffusion of GFP in L. lactis drops by two orders of magnitude when the medium osmolality is increased by ∼ 1.9 Osm, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 57 publications
(120 reference statements)
1
36
0
Order By: Relevance
“…For example, osmotic reversal experiments indicated that most of the growing hyphal tips were inactivated during the first 10 min on high-osmolality medium, but both the DivIVA-EGFP foci and the FilP cytoskeletal structures appeared to be immobile for the first 100 min after osmotic upshift and disappeared during the dynamic adaptation period before regrowth. Mika et al have shown that a 15% reduction in cell volume in L. lactis upon osmotic upshift was accompanied by a drop of the diffusion coefficient by almost two orders of magnitude (43). It might be challenging for the cell without fluidization of the cytoplasm to recover from the static state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, osmotic reversal experiments indicated that most of the growing hyphal tips were inactivated during the first 10 min on high-osmolality medium, but both the DivIVA-EGFP foci and the FilP cytoskeletal structures appeared to be immobile for the first 100 min after osmotic upshift and disappeared during the dynamic adaptation period before regrowth. Mika et al have shown that a 15% reduction in cell volume in L. lactis upon osmotic upshift was accompanied by a drop of the diffusion coefficient by almost two orders of magnitude (43). It might be challenging for the cell without fluidization of the cytoplasm to recover from the static state.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the time until recovery of growth is determined by the recovery of the ability of the proteins to diffuse in the cytoplasm (12). Indeed, the diffusion constants of GFP in individual cells suffering an osmotic upshift have been shown to decrease by more than an order of magnitude, both in Gram-negative E. coli and Gram-positive Lactococcus lactis (12,43,44). Konopka et al found that in severely plasmolyzed E. coli cells, diffusion of GFP was unexpectedly slow and could not be explained by molecular crowding only (12).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we need to acknowledge the large differences in lateral diffusion coefficients between model membranes such as are found in giant unilamellar vesicles where the values of diffusion coefficients for membrane proteins are 1-10 µm 2 /s [52] and those in native membranes where membrane proteins are characterized by diffusion coefficients that are several of orders of magnitude lower with values of 0.01-0.1 µm 2 /s. [53,54,55,50] However, these measurements are more nuanced than first meets the eye and the results for several membrane proteins have been shown to depend upon the time scales over which the diffusion is characterized. [54] In particular, using the FCS method which probes diffusion on short length and time scales, both the TAR receptor and TetA (a tetracycline antiporter) were found to have diffusion constants of 4.2 µm 2 /s and 9.1 µm 2 /s, respectively, to be contrasted with the values of 0.017 µm 2 /s and 0.086 µm 2 /s, respectively found when using the FRAP measurement.…”
Section: The Dynamic Membranementioning
confidence: 99%
“…The cellular microenvironment and molecular crowding are key physicochemical characteristics of cellular bodies with a high macromolecular content (Gnutt et al, 2015;Hancock, 2004;Matera et al, 2009;Richter et al, 2007;Richter et al, 2008), and diffusion coefficients (Ds) of fluorescent probe molecules such as green fluorescent protein (GFP) in live cells have been systematically characterized to investigate these traits (Finan et al, 2011;Hihara et al, 2012;Konopka et al, 2009;Mika et al, 2014;Park et al, 2015;Schavemaker et al, 2018;Verkman, 2002). In particular, observations using FCS suggested that heterochromatin and mitotic chromosomes are accessible to protein factors with a molecular size up to 150 kDa, despite their densely packed structure (Hihara et al, 2012).…”
Section: Introductionmentioning
confidence: 99%